2017
DOI: 10.3389/fcimb.2017.00123
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma Species Multiple Banded Antigen (MBA) Variation Is Associated with the Severity of Inflammation In vivo and In vitro in Human Placentae

Abstract: Background: The multiple banded antigen (MBA), a surface-exposed lipoprotein, is a proposed virulence factor of Ureaplasma spp. We previously demonstrated that the number of Ureaplasma parvum MBA size variants in amniotic fluid was inversely proportional to the severity of chorioamnionitis in experimentally infected pregnant sheep. However, the effect of ureaplasma MBA size variation on inflammation in human pregnancies has not been reported.Methods: Ureaplasmas isolated from the chorioamnion of pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…These inflammatory responses seemed to be associated with the expression of MBA size variants in Ureaplasma spp. Recent studies have shown an inverse relationship between a higher number of MBA size variants in the amniotic fluid or placenta and severity of chorioamnionitis . To prevent eradication by maternal immune response, MBA size variation may also be a mechanism used by Ureaplasma spp …”
Section: Genital Ureaplasma Infection and Preterm Birthmentioning
confidence: 99%
“…These inflammatory responses seemed to be associated with the expression of MBA size variants in Ureaplasma spp. Recent studies have shown an inverse relationship between a higher number of MBA size variants in the amniotic fluid or placenta and severity of chorioamnionitis . To prevent eradication by maternal immune response, MBA size variation may also be a mechanism used by Ureaplasma spp …”
Section: Genital Ureaplasma Infection and Preterm Birthmentioning
confidence: 99%
“…Gram‐positive bacteria (e.g., Listeria, GBS, and Ureaplasma species) are pathogens commonly associated with PTB . However, competency of certain bacteria to trigger PTB remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Gram-positive bacteria (e.g., Listeria, GBS, and Ureaplasma species) are pathogens commonly associated with PTB. 5,6,[12][13][14][15] However, competency of certain bacteria to trigger PTB remains unclear. Although all experimental models of PTB have limitations compared to human pregnancy and parturition, mice represent the most common animal model of PTB.…”
Section: Activation Of Tlr2 By Pam2cys But Not Pam3cys Induces Ptbmentioning
confidence: 99%
See 2 more Smart Citations